2022
DOI: 10.1007/s10291-022-01384-3
|View full text |Cite
|
Sign up to set email alerts
|

Fast satellite selection algorithm for GNSS multi-system based on Sherman–Morrison formula

Abstract: Efficient use of global navigation satellite system (GNSS) observations improves when applying rational satellite selection algorithms. By combining the Sherman–Morrison formula and singular value decomposition, a smaller-GDOP (geometric dilution of precision)-value method is proven for an increasing number of visible satellites. By combining this smaller-GDOP-value method with the maximum-volume-tetrahedron method, a new rapid satellite selection algorithm based on the Sherman–Morrison formula for GNSS multi-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Combined with the results of the "Analysis of the SVOP Values" subsection, it can be concluded that the deployment of 4 satellites in each orbit cannot meet the real-time positioning requirements. In order to achieve the real-time positioning effect of the 3-orbit lunar GNSS constellation, combining the constellation composition of GNSS with the theory of satellite selection 18 , and considering the satellite launch and operation cost, let each orbit has 5 satellites, a total of 15 satellites. The satellites of one orbit are evenly distributed in the orbit, and the phase difference of the adjacent satellites is 10  in the different Halo orbits.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with the results of the "Analysis of the SVOP Values" subsection, it can be concluded that the deployment of 4 satellites in each orbit cannot meet the real-time positioning requirements. In order to achieve the real-time positioning effect of the 3-orbit lunar GNSS constellation, combining the constellation composition of GNSS with the theory of satellite selection 18 , and considering the satellite launch and operation cost, let each orbit has 5 satellites, a total of 15 satellites. The satellites of one orbit are evenly distributed in the orbit, and the phase difference of the adjacent satellites is 10  in the different Halo orbits.…”
Section: Resultsmentioning
confidence: 99%
“…The initial approach involves determining the optimal satellite combination by assessing the influence of currently observable satellites on the overall GDOP. Subsequently, a recursive strategy is employed to finalize the optimal satellite constellation [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%